PENGETAHUAN DAN SIKAP BIDAN TERHADAP PENERAPAN INISIASI MENYUSU DINI - Ummi Kaltsum S. Saleh; B. Bakoil, Mareta; Kalzum Kiah, Firda; L. Manalor, Loriana (Midwifery And Complementary Care, 2025)
Background: Early initiation of breastfeeding (EIBF) is the practice of providing breast milk within the first hour after birth. It is proven to reduce neonatal mortality and improve infant nutritional status. However, the implementation of EIBF has not been fully adopted by healthcare workers, including midwives. Objective: This study aimed to analyze the relationship between midwives’ level of knowledge and attitudes with the implementation of early initiation of breastfeeding at Prof. Dr. W. Z. Johannes General Hospital in Kupang. Methods: This was an analytical study with a cross-sectional design. The sample consisted of 21 midwives selected using total sampling. Data were collected using questionnaires to assess knowledge and attitudes, and observations using a checklist to evaluate EIBF implementation. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Results: Most midwives had good knowledge (90.5%) and positive attitudes (57%) regarding EIBF. However, only 33% of respondents implemented EIBF. The statistical test showed no significant relationship between knowledge (p = 0.533) or attitude (p = 0.642) and the implementation of EIBF. Conclusion: There is no significant relationship between midwives’ knowledge and attitudes and the implementation of early initiation of breastfeeding. Continuous training and capacity-building programs are recommended to support midwives in implementing EIBF according to established guidelines. Keywords: Midwife, Knowledge, Attitude, Early Breastfeeding Initiation